2022
DOI: 10.3389/fchem.2022.955065
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Doped g-C3N4 Photocatalyst for Solar Water Splitting: A Review

Abstract: Graphitic carbon nitride (g-C3N4) photocatalysis for water splitting is harvested as a fascinating way for addressing the global energy crisis. At present, numerous research subjects have been achieved to design and develop g-C3N4 photocatalysis, and the photocatalytic system still suffers from low efficiency that is far from practical applications. Here, there is an inspiring review on the latest progress of the doping strategies to modify g-C3N4 for enhancing the efficiency of photocatalytic water splitting,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Especially, g-C 3 N 4 with a narrow band gap (∼2.7 eV) is capable of harvesting visible light, and its band edge positions are suitable for water splitting. 20–22 In 2009, Wang et al 23 first showed photocatalytic H 2 production from water using g-C 3 N 4 as the photocatalyst under visible light irradiation. The result of Wang's study motivated the researchers to further explore and improve the photocatalytic H 2 production performance of g-C 3 N 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Especially, g-C 3 N 4 with a narrow band gap (∼2.7 eV) is capable of harvesting visible light, and its band edge positions are suitable for water splitting. 20–22 In 2009, Wang et al 23 first showed photocatalytic H 2 production from water using g-C 3 N 4 as the photocatalyst under visible light irradiation. The result of Wang's study motivated the researchers to further explore and improve the photocatalytic H 2 production performance of g-C 3 N 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Photoelectrochemical water splitting is one of the most promising methods since Honda and Fujishima succeeded water-splitting using a TiO 2 photoanode in 1972 . Since then, various materials such as Fe 2 O 3 , Cu 2 O, BiVO 4 , SrTiO 3 , C 3 N 4 have been proposed as candidates of photocatalytic materials in the last few decades and gradually the conversion efficiency has been improved, and their underlying physical mechanisms have been clarified. , Furthermore, a combination of materials has been explored for efficient charge carrier separation. The “Z-scheme” photocatalyst is composed of p-type and n-type semiconductors to separate the hydrogen and oxygen reaction sites. “Heterojunction” is used for efficient directional charge separation due to the band alignment. For efficient charge transfer at the solution interfaces, a variety of cocatalysts have been examined and optimized for each material. , In recent years, facet-selected photocatalysis has been synthesized because oxidation and reduction reactions are preferred at each different surface. In spite of these efforts, the efficiencies and lifetime of these materials are not sufficient for practical applications in terms of cost, stability, and safety.…”
Section: Introductionmentioning
confidence: 99%
“…[46][47][48] Heteroatom doping can be used to change the electronic structure of the substrate material through orbital modulation or charge redistribution without changing the desired intrinsic characteristics, structure or composition of the substrate material. [49][50][51] Doping with W is one of the effective ways to improve the catalyst activity, mainly by enhancing the interaction of the catalyst with intermediates during the reaction. Meanwhile, W doping can change the electronic structure of the catalyst and improve the electron conductivity and transmission efficiency.…”
Section: Introductionmentioning
confidence: 99%